2021
DOI: 10.3390/gels7020070
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Human Myocardium Derived Decellularized Extracellular Matrix for 3D Bioprinting and Cardiac Tissue Engineering

Abstract: The generation of 3D tissue constructs with multiple cell types and matching mechanical properties remains a challenge in cardiac tissue engineering. Recently, 3D bioprinting has become a powerful tool to achieve these goals. Decellularized extracellular matrix (dECM) is a common scaffold material due to providing a native biochemical environment. Unfortunately, dECM’s low mechanical stability prevents usage for bioprinting applications alone. In this study, we developed bioinks composed of decellularized huma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 65 publications
0
64
0
Order By: Relevance
“…The constructs exhibited contractile function. Cardiac tissue-derived ECM has also been shown to promote in vitro differentiation and maturation of cardiomyocytes derived from human embryonic stem cells or human induced pluripotent stem cells [78,79]. Bosara et al developed hydrogels using decellularized human myocardium-derived ECM with gelatin methacryloyl (GelMA) or GelMA-methacrylated hyaluronic acid (MeHA).…”
Section: Ecm-based Biomaterialsmentioning
confidence: 99%
“…The constructs exhibited contractile function. Cardiac tissue-derived ECM has also been shown to promote in vitro differentiation and maturation of cardiomyocytes derived from human embryonic stem cells or human induced pluripotent stem cells [78,79]. Bosara et al developed hydrogels using decellularized human myocardium-derived ECM with gelatin methacryloyl (GelMA) or GelMA-methacrylated hyaluronic acid (MeHA).…”
Section: Ecm-based Biomaterialsmentioning
confidence: 99%
“…The extrusion-based method is commonly used in bioprinting due to superior print speed [87]. Bioprinting ushers' advantages, including patient-derived anatomical shape via computed tomography (CT) images, forming complex organization structure of desired tissue, manipulating cell distribution in a printed construct (Figure 2I,j) [88][89][90]. Furthermore, the effect of Notch signaling inhibition on a bioprinted cardiac patch was studied.…”
Section: Bioprintingmentioning
confidence: 99%
“…In recent years, the rapid development of 3D printing technology enabled the construction of hydrogels and myocardial patches into highly precise and repeatable nanoscale 3D structures using multiple cell types. Biomaterials that are used for the 3D printing of myocardial tissue include alginate [93,94], fibrin [94], collagen [95,96], gelatin [97][98][99], hyaluronic acid [98], hydroxypropyl chitin [100], thixotropic magnesium phosphate [101], gellan gum [99], and decellularized ECM scaffolds [102][103][104]. Maiullari et al manufactured a vascularized heart tissue using human umbilical vein endothelial cell (HUVEC) and miPSC-CMs using alginate and PEG/fibrin hydrogel extruded through a microfluidic printing head [94].…”
Section: D Printing In Cardiac Tissue Engineering Using Psc Derived Cardiovascular Cellsmentioning
confidence: 99%
“…This tissue-specific bioink may provide crucial cues for improving cell engraftment, survival, and function. Bioinks composed of decellularized human heart tissue with either gelatin methacryloyl (GelMA) or GelMA-methacrylated hyaluronic acid (MeHA) hydrogels were developed [104]. It was observed that all bioinks were compatible with hiPSC-CMs and human cardiac fibroblasts.…”
Section: D Printing In Cardiac Tissue Engineering Using Psc Derived Cardiovascular Cellsmentioning
confidence: 99%